Pre-existing treatment with aspirin or statins influences clinical presentation, infarct size and inflammation in patients with de novo acute coronary syndromes. (15th January 2019) - Weidmann, Lukas; Obeid, Slayman; Mach, François; Shahin, Mohammady; Yousif, Nooraldaem; Denegri, Andrea; Muller, Olivier; Räber, Lorenz; Matter, Christian M.; Lüscher, Thomas F.
Abstract: Background: Influence of pre-existing treatment with aspirin and/or statins prior to a first acute coronary syndrome (ACS) on clinical presentation, infarct size and inflammation markers. We analyzed patients from the Swiss Program University Medicine ACS -cohort (SPUM-ACS; ClinicalTrials.gov number: NCT01075867 ). Methods: 1639 patients were categorized into 4 groups: (1) patients without either drug (n = 1181); (2) patients only on aspirin (n = 157); (3) patients only on statins (n = 133) and (4) patients on both drugs (n = 168). Clinical features, electrocardiogram (ECG), creatinine kinase (CK, U/l), high-sensitivity troponin T (hsTNT, μg/l), N-terminal brain natriuretic peptide (NT-proBNP, ng/l), leucocytes (Lc, G/l), neutrophils (Nc, G/l), C-reactive protein (CRP, mg/l) and angiographic features were documented at baseline. Results: Incidences of ST-elevation myocardial infarction (STEMI) were 64% in group 1, 45% in group 2, 52% in group 3 and 40% in group 4 ( p < 0.0001). Those with both drugs had significantly lower CK (median 145 U/l, interquartile range (IQR) 89–297), hsTNT (median 0.13 μg/l, IQR 0.03–0.52) and higher left ventricular ejection fraction values (LVEF) (mean 55 ± 12%) compared to untreated patients (median CK 273 U/l, IQR 128–638; median hsTNT 0.26 μg/l, IQR 0.08–0.85; mean LVEF 51 ± 11%) ( p < 0.0001, p = 0.001, p = 0.028, respectively). Co-medicated groups matched for high risk factors presented less frequently as STEMIs ( p < 0.0001), had significantly smaller infarcts determined by CK and hsTNT (both p < 0.0001) and lower CRP levels ( p = 0.01) compared to patients without pre-existing treatment with either drug. Conclusion: Pre-existing treatment with aspirin and/or statins and particularly with their combination changes the clinical presentation, infarct size, inflammation markers and LVEF in patients suffering their first ACS. Highlights: Pre-existing treatment with aspirin and statins seems to decrease the rate of STEMI. Aspirin and statins influence on CK and troponin T levels at presentation of ACS Aspirin and statins influence on systemic inflammation reaction during ACS Aspirin and statin treatment influences on ejection fraction during angiography